Does the Pressure of Population and Poverty cause Deforestation? - Widiaryanto, Pungky (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
Deforestation has created several negative impacts such as reducing biodiversity, decreasing life support system and increasing green house gases emission. Identifying the causes of deforestation is a key to tackle this problem. Various studies have been conducted to investigate the driver of deforestation in the world. Some experts believe that the pressure of population and poverty cause deforestation. On the other hand, the others argue that there is no relationship among the pressure of population, poverty and deforestation. This paper tries to examine the link of pressure of population, poverty and deforestation by reviewing some recent studies.